The Function of FoxK Transcription Factors in Diseases - Yu, Mujun; Yu, Haozhen; Mu, Nan; Wang, Yishi; Ma, Heng; Yu, Lu (Frontiers in Physiology, 2022)
Forkhead box (FOX) transcription factors play a crucial role in the regulation of many diseases, being an evolutionarily conserved superfamily of transcription factors. In recent years, FoxK1/2, members of its family, has been the subject of research. Even though FoxK1 and FoxK2 have some functional overlap, increasing evidence indicates that the regulatory functions of FoxK1 and FoxK2 are not the same in various physiological and disease states. It is important to understand the biological function and mechanism of FoxK1/2 for better understanding pathogenesis of diseases, predicting prognosis, and finding new therapeutic targets. There is, however, a lack of comprehensive and systematic analysis of the similarities and differences of FoxK1/2 roles in disease, prompting us to perform a literature review.